(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the results of studying the amount of iron contained in Triticum aestivum L. varieties grown in the fields of the Kashkadarya region. It has been established that the ancient local wheat varieties “Kyzyl Shark” and “Kyzyl Shalola”, as well as the “Gozgon” variety, cultivated over large areas in the region, have a high content of the iron element. It is concluded that the use of ancient local varieties of T. aestivum in biofortification makes it possible to create highly specialized varieties enriched with minerals. As a result, it is possible to provide all segments of the population with a safe, effective and cost-effective form of iron to combat anemia.